A novel non-contrast-enhanced MRA using silent scan for evaluation of brain arteriovenous malformation: A case report and review of literature. Issue 45 (November 2017) - Moon, Jin Il; Baek, Hye Jin; Ryu, Kyeong Hwa; Park, Hyun
Abstract: Rationale: Brain arteriovenous malformations (AVMs) are congenital vascular abnormalities involving abnormal connections between arteries and veins. In clinical practice, imaging studies help evaluate feeding arteries, niduses, draining venous systems, and coexisting complications in patients with brain AVM. They also have an impact on decision-making regarding clinical management. We applied a novel non-contrast-enhanced MR angiography (MRA) technique, termed "silent MRA, " for evaluating an incidental brain AVM. Here, we describe the clinical case with radiological review and highlight the technical background and clinical usefulness of silent MRA. Patient concerns: A 60-year-old woman underwent neuroimaging study including MRA to evaluate intracranial cause of headache. Diagnoses: The brain AVM, including its nidus and draining veins, was conspicuously delineated on silent MRA images; these findings correlated well with conventional angiographic findings. Interventions: The patient did not receive interventional or surgical treatment. Outcomes: The patient is being followed up regularly at the outpatient department. Lessons: The silent MRA can be a suitable imaging modality for repeated follow-up evaluation for not only brain AVMs but also various intracranial vascular diseases without the use of contrast materials.